First, expand the terms in parenthesis on the left side of the equation by multiplying each term within the parenthesis by the term outside the parenthesis:
#color(red)(3)(x + 3) = 5 - 2x#
#(color(red)(3) xx x) + (color(red)(3) xx 3) = 5 - 2x#
#3x + 9 = 5 - 2x#
Next, subtract #color(red)(9)# and add #color(blue)(2x)# from each side of the equation to isolate the #x# term while keeping the equation balanced:
#3x + color(blue)(2x) + 9 - color(red)(9) = 5 - color(red)(9) - 2x + color(blue)(2x)#
#(3 + color(blue)(2))x + 0 = -4 - 0#
#5x = -4#
Now, divide each side of the equation by #color(red)(5)# to solve for #x# while keeping the equation balanced:
#(5x)/color(red)(5) = -4/color(red)(5)#
#(color(red)(cancel(color(black)(5)))x)/cancel(color(red)(5)) = -4/5#
#x = -4/5#